Pengaruh Literasi Investasi dan Teknologi Terhadap Keputusan Investasi - Tri Mahendra, Prasetya; Novaliana, Ika; Suwandi (JURNAL EKUIVALENSI, 2024)
Technological advances have created a modern era characterized by economic growth, social mobility, and cultural expansion. Thanks to technology, many market players or companies utilize it as a means of channeling their business goals and securities companies also create investment applications. With the availability of the internet, information about the advantages and disadvantages of investment is increasingly easy to obtain. The purpose of this study was to examine the effect of technology and investment knowledge on student investment decisions. The population and samples used are students of Sekolah Tinggi Ilmu Ekonomi (STIE) Nganjuk who have carried out investment activities at the Indonesia Stock Exchange Investment Gallery. Data collection was carried out by distributing questionnaires using Likert scale measurements. The data testing techniques used are validity test and reliability test, r-square test, and hypothesis testing using SmartPLS 3.2.4 software. The results showed that investment literacy has a positive and significant effect on investment decisions, while technology has a negative effect on investment decisions. The better the investment literacy of students in the capital market, the more it will affect the decision to invest.